Social Acknowledgment of Violent Experiences and Its Role in PTSD and Appetitive Aggression Among High-Risk Males in South Africa. (January 2017) - Sommer, Jessica; Hinsberger, Martina; Weierstall, Roland; Holtzhausen, Leon; Kaminer, Debra; Seedat, Soraya; Maercker, Andreas; Madikane, Solomon; Elbert, Thomas
Violence exposure poses a risk for posttraumatic stress disorder (PTSD) and appetitive aggression. Does acknowledgment of violent experiences by one's social environment also affect these adverse consequences of violence? We investigated relations between number of traumatic event types, number of violent offenses, PTSD symptoms, appetitive aggression, and social acknowledgment. A total of 290 participants were recruited through a Cape Town rehabilitation center for offenders. Using path analysis, we demonstrate higher societal disapproval to be associated with more intense PTSD symptoms and greater appetitive aggression. However, past experiences of recognition were also related to more intense PTSD symptoms. Violence exposure was positively associated with PTSD symptoms and appetitive aggression, and a higher number of violent offenses was related to greater appetitive aggression. Results indicate that besides violence exposure, social acknowledgment may play a significant role in the severity of PTSD and appetitive aggression. Intervention programs should not neglect targeting social structures.